Single‐Step Anodization for the Formation of WO3‐Doped TiO2 Nanotubes Toward Enhanced Electrochromic Performance. Issue 22 (11th September 2018) - Yoo, Hyeonseok; Oh, Kiseok; Nah, Yoon‐Chae; Choi, Jinsub; Lee, Kiyoung
Abstract: Herein, we report a single‐step anodization process for WO3 ‐doped TiO2 nanotubes in an aqueous electrolyte containing the tungsten precursor Na2 WO4 ⋅ 2H2 O and fluoride ions. The single‐step anodization allows for homogeneous doping of WO3 into the TiO2 nanotube structures. The doping concentration depends on the concentration of the tungsten precursor in the electrolyte, demonstrating that the reported anodizing process is the most efficient approach for metal oxide doping in TiO2 . Moreover, compared to bare TiO2, the WO3 ‐doped TiO2 nanotubes shows better proton intercalation, which leads to enhanced electrochromic performance. Abstract : Single‐step performance boost : the feasibility of obtaining WO3 ‐doped TiO2 nanotubes by single‐step anodization of Ti in a tungstate‐containing electrolyte is demonstrated. The doping concentrations are controlled by concentration of tungstate salt in the electrolyte. The doped TiO2 nanotubes allow for higher electrochromic activity as compared with that of bare TiO2 structures.